(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
In the highly competitive retail industry, an understanding on the perceptions of shoppers is important in attracting and retaining loyal customers. This study compares the shoppersâ€™ perceptions on various image dimensions using KSL City and Plaza Pelangi in Johor Bahru, Malaysia as case studies. Plaza Pelangi is more established but faces high vacancy rate and competition from KSL City. The latter is relatively new and needs to capture the shoppers market from Plaza Pelangi. A total 200 questionnaires were distributed using random sampling. Wilcoxon Signed Ranks Test, Paired-Samples T Test, Chi Square Test, One Way ANOVA were used. There was no significant difference between the overall preferences towards both shopping centers. However, there were significant differences according to demographic groups (race, age and marital status). Majority of the image dimension attributes were rated higher in KSL City compared to Plaza Pelangi. KSL City needs to improve the ease in locating merchandise and appoint higher quality tenants.Â KSL should strive for more inclusive shopper demographic groups. Plaza Pelangi needs to improve its physical dimension in terms of layout and facility dimension by undergoing upgrading works. Plaza Pelangi also needs to recruit more food and beverage outlets as well as entertainment outlets.